2002
DOI: 10.1002/clc.4960250410
|View full text |Cite
|
Sign up to set email alerts
|

New parameters in the interpretation of exercise testing in women: QTC dispersion and QT dispersion ratio difference

Abstract: SummaryBackground: It has been reported that the increase of QT dispersion (QTD) that occurs due to increased inhomogeneity of the ventricular repolarization because of transient ischemia obtained by standard 12-lead electrocardiogram (ECG), the changes during exercise, and the differences between exercise and rest increase the accuracy of exercise test in the diagnosis of coronary artery disease (CAD).Hypothesis: This study was designed to investigate the value of QTD parameters, which are reported to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We believe temporary ischemia might prolong the QT interval in these patients. Furthermore, Ozdemir et al found that QT dispersion in female patients increased the diagnostic value of EET [20]. As our study was not designed to address the issue and patients with negative EET were not included, information about QTc and QT disp in the patients with negative exercise test and critical CAD is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…We believe temporary ischemia might prolong the QT interval in these patients. Furthermore, Ozdemir et al found that QT dispersion in female patients increased the diagnostic value of EET [20]. As our study was not designed to address the issue and patients with negative EET were not included, information about QTc and QT disp in the patients with negative exercise test and critical CAD is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The lead of a standard ECG with the shortest QT interval indicates the area of earliest repolarization, whereas the lead with the longest QT interval represents the area of the ventricular myocardium that is last to repolarize. [15][16][17][18][19][20][21][22][37][38][39][40][41][42][43][44][45] Also, increased QTd is associated with malignant ventricular arrhythmias [9][10][11]46 and sudden cardiac death. It has been proposed as a marker of heterogeneous repolarization and electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…36 Different studies have shown that QTd is abnormally increased in patients with acute or remote myocardial infarction, acute coronary syndrome, vasospastic angina, syndrome X, exercise induced myocardial ischemia, heart failure and ventricular hypertrophy, and during balloon angioplasty. [15][16][17][18][19][20][21][22][37][38][39][40][41][42][43][44][45] Also, increased QTd is associated with malignant ventricular arrhythmias [9][10][11]46 and sudden cardiac death. [37][38][39]41,42,47 In a previous study of patients with 3-vessel disease, 43 it has been demonstrated that the severity or extent of myocardial ischemia induced by using atrial pacing was related to the degree of induced changes of the QTd.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been expressed to explain the high false positive rate of ST-segment depression in women, including the fact that estrogen has a chemical structure similar to digitalis during exercise, this is responsible for the high prevalence of false-positive test results in women and causes differences in accuracy of ST segment depression in women compared to men. 7 Antiplatelet was used in almost all subjects with significant lesions and only 44.2% in the group with insignificant lesions. Beta blockers, and statins are also used in almost all subjects with significant lesions, because the use of beta blockers in cases of CAD is needed for anti-ischemic and statin for stabilisation of plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of the parameters ∆QTcD and ∆QTdR at the time TMT can provide better sensitivity to detect ischemic responses in patients with stable angina pectoris than only using conventional criteria that have been previously set. [5][6][7][8]…”
Section: Indonesian Journal Of Cardiologymentioning
confidence: 99%